2022
DOI: 10.3389/fimmu.2021.798683
|View full text |Cite
|
Sign up to set email alerts
|

An Emerging Role of TIM3 Expression on T Cells in Chronic Kidney Inflammation

Abstract: T cell immunoglobulin domain and mucin domain 3 (TIM3) was initially identified as an inhibitory molecule on IFNγ-producing T cells. Further research discovered the broad expression of TIM3 on different immune cells binding to multiple ligands. Apart from its suppressive effects on the Th1 cells, recent compelling experiments highlighted the indispensable role of TIM3 in the myeloid cell-mediated inflammatory response, supporting that TIM3 exerts pleiotropic effects on both adaptive and innate immune cells in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 111 publications
(114 reference statements)
0
5
0
Order By: Relevance
“…Monoclonal anti-Tim-3 antibody was reported to be protective in the ischemia/reperfusion injury mice model [ 14 ]. In a clinical case with Mycobacterium tuberculosis infection, the high Tim-3 expression in CD3-positive circulating T cells was related to the progression of inflammatory kidney injury [ 15 ]. High expression of Tim-3 and low expression of Heme oxygenase-1 (HO-1) were also found in skin tissue from SARS-CoV-2 positive patients [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Monoclonal anti-Tim-3 antibody was reported to be protective in the ischemia/reperfusion injury mice model [ 14 ]. In a clinical case with Mycobacterium tuberculosis infection, the high Tim-3 expression in CD3-positive circulating T cells was related to the progression of inflammatory kidney injury [ 15 ]. High expression of Tim-3 and low expression of Heme oxygenase-1 (HO-1) were also found in skin tissue from SARS-CoV-2 positive patients [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…These outcomes align with prior research that posits an increase in TIM-3 expression in T cells following infection ( 29 ). Our prior investigations have demonstrated that CD3+TIM-3+ T cells may not play an anti-inflammatory role in the context of chronic infection, but instead, promote inflammation ( 30 ). Moreover, our research has revealed that patients with diabetes who have developed DR, DPN, or other glomerular nephropathy exhibit down-regulation of LAG-3 on peripheral T lymphocyte compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…This present study ties Gal-9 and its receptor, Tim-3, to the pathogenesis of renal IRI. Tim-3 signaling pathway is associated with acute and chronic kidney in ammation [41,42]. Abnormal Tim-3 expression can be detected on the surface of renal parenchymal cells or immune cells in IgA nephropathy [43], lupus nephritis [44], diabetic nephropathy [45], renal tumor [46], and renal transplantation rejection [47].…”
Section: Discussionmentioning
confidence: 99%